130 Prior coronary artery bypass graft patients treated with primary percutaneous coronary intervention have higher long-term adverse event rates. (16th May 2012) - Hamshere, S M; Jones, D A; Akhtar, M; Rathod, K S; Graham, A; Guttmann, O; Gallagher, S; Jain, A; Knight, C; Mathur, A; Wragg, A
Abstract : Background: Limited information exists regarding procedural success and clinical outcomes of ST-segment elevation myocardial infarction (STEMI) patients with previous CABG undergoing primary PCI. We sought to compare outcomes in STEMI patients undergoing primary percutaneous coronary intervention (PCI) with or without previous coronary artery bypass grafts (CABG). Methods: Clinical information was analysed from a prospective database on 2322 STEMI patients who underwent Primary PCI between January 2004 and May 2010 at a London centre. 104 of 2322 (4.5%) patients had prior CABG. MACE was defined as a composite of death, stroke and target vessel revascularisation (TVR). Outcome assessed by all-cause mortality information provided by the Office of National Statistics via the BCIS CCAD national audit. Results: Patients with previous CABG were older, had more associated comorbidity and a higher incidence of multivessel coronary disease than patients who have never had CABG. In patients with previous CABG, the infarct related artery (IRA) was split evenly between a bypass graft (n=50) and a native vessel (n=54). Procedural success (defined as TIMI 3 flow at the end of procedure) was less likely in patients with previous CABG 84.5% vs 95.6% (p<0.0001) than in patients who had never undergone CABG. Patients with previous CABG had more MACE (32.8% vs 16.5%, p=0.01) during the 4-year follow-up period (Abstract 130 figure 1 ). After multivariable adjustment this difference persisted (HR 2.2, 95% CI 1.26 to 3.78, p=0.02). When stratifying prior CABG patients by the type of IRA (Abstract 130 figure 2 ); Long term MACE were significant more likely in patients who had bypass graft PCI than in patients that had native vessel PCI (44.6% vs 19.8%, p=0.04). Conclusions: Previous CABG patients with STEMI treated with primary PCI have higher long-term adverse events. The long-term event rates are higher still if the IRA is a bypass graft.